Photogrammetry requirements for digital camera calibration applying Tcc and MatLab software - Sužiedelytė-Visockienė, Jūratė (Geodesy and Cartography, 2012)
The result of photogrammetry is a digital object or terrain images on the plane or in three-dimensional space. Precise data on the object is photocopied by a professional digital camera equipped with the calibrated system of optical lens (evaluation of distortion parameters for optical lens). Camera calibration is performed in a laboratory or employing special calibration software and using special field testing. However, Lithuania doesn’t own similar laboratories. Therefore, an important point is obtaining proper software for the verification of these works. European countries have been using plenty of various software and different test field calibration (plate), including two-dimensional, three-dimensional, etc. Therefore, choosing the simplest, cheapest and most acceptable method of camera calibration is essential. Research was made applying the Canon EOS-1D Mark II (resolution - 21 million points, with the focal length of the lens reaching 21 mm). The optical system was calibrated using Tcc (Germany) and MatLab software. The calibration processes were done taking a different test field of camera calibration. The article analyzes calibration results and offers suggestions on camera calibration.